2020
DOI: 10.2147/ott.s225661
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Noncoding RNA X-Inactive Specific Transcript Facilitates Cellular Functions in Melanoma via miR-139-5p/ROCK1 Pathway</p>

Abstract: Although X-inactive specific transcript (XIST) is known to play a critical role in the pathogenesis of melanoma, the mechanisms through which this remains unclear. Methods: RNAseq, immunohistochemistry, and qRT-PCR were used to identify the levels of XIST, miR-139-5p, and Rho-Associated Coiled-Coil Containing Protein Kinase-1 (ROCK1) in melanoma tissues and cells. A subcellular fractionation assay was used to determine the location of XIST. CCK-8 and colony formation assays were used to evaluate cellular proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Notably, XIST upregulation has been observed in some malignant tumors and was found to be associated with tumor cell growth, infiltration, and migration, higher TNM staging, and positive lymph node metastasis. 18 XIST has been shown to function as a “molecular sponge” of miR-139-5p in melanoma, 19 regulate the miR-133a/SOX4 axis in glioma 20 and miR-497 in gastric cancer, 11 and promote cell proliferation, invasion, and metastasis. In addition, XIST methylation status has been reported to modulate prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, XIST upregulation has been observed in some malignant tumors and was found to be associated with tumor cell growth, infiltration, and migration, higher TNM staging, and positive lymph node metastasis. 18 XIST has been shown to function as a “molecular sponge” of miR-139-5p in melanoma, 19 regulate the miR-133a/SOX4 axis in glioma 20 and miR-497 in gastric cancer, 11 and promote cell proliferation, invasion, and metastasis. In addition, XIST methylation status has been reported to modulate prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The role of XIST in cancer has also been widely reported. Tian et al showed that XIST was highly expressed in melanoma cells 39 . Overexpression of XIST can promote the proliferation, migration, and invasion of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…miR-139-5p expression was significantly downregulated and positively correlated with ROCK1 expression during Ewing sarcoma progression ( 35 ). Moreover, the lncRNA X-inactive specific transcript was found to sponge miR-139-5p, thereby reducing the levels of ROCK1( 36 ). In the present study, miR-139-5p expression was reduced in the mice with sepsis-induced lung injury, whereas ROCK1 expression was significantly increased.…”
Section: Discussionmentioning
confidence: 99%